Cortical thickness and brain volumetric analysis in body dysmorphic disorder. Issue 1 (30th April 2015) - Madsen, Sarah K.; Zai, Alex; Pirnia, Tara; Arienzo, Donatello; Zhan, Liang; Moody, Teena D.; Thompson, Paul M.; Feusner, Jamie D.
Abstract: Individuals with body dysmorphic disorder (BDD) suffer from preoccupations with perceived defects in physical appearance, causing severe distress and disability. Although BDD affects 1–2% of the population, the neurobiology is not understood. Discrepant results in previous volumetric studies may be due to small sample sizes, and no study has investigated cortical thickness in BDD. The current study is the largest neuroimaging analysis of BDD. Participants included 49 medication-free, right-handed individuals with DSM-IV BDD and 44 healthy controls matched by age, sex, and education. Using high-resolution T1-weighted magnetic resonance imaging, we computed vertex-wise gray matter (GM) thickness on the cortical surface and GM volume using voxel-based morphometry. We also computed volumes in cortical and subcortical regions of interest. In addition to group comparisons, we investigated associations with symptom severity, insight, and anxiety within the BDD group. In BDD, greater anxiety was significantly associated with thinner GM in the left superior temporal cortex and greater GM volume in the right caudate nucleus. There were no significant differences in cortical thickness, GM volume, or volumes in regions of interest between BDD and control subjects. Subtle associations with clinical symptoms may characterize brain morphometric patterns in BDD, rather than large group differences in brain structure. Highlights: Brain structure was assessed in body dysmorphic disorder (BDD) and controls. We tested associations with clinical scores in BDD No significant group differences were found. Worse anxiety in BDD is associated with localized gray matter differences. BDD may be characterized by subtle associations with clinical features, rather than widespread morphometric abnormalities.